Utilization of Cow Manure into Compost in Gunung Keling Village - Michael Sudyanto; Michaella Christina; Alexxys Mirelle; Deano Narta; Gracia Adelia (Green Publisher Indonesia, 2025)
Gunung Keling Village, located in Cigugur Subdistrict, Kuningan Regency, West Java, has great potential for managing dairy cattle waste into organic fertilizer, as there are about 700 cows in the village. BUMDes Gunung Keling was established in 2018 to support the village’s economic development, but it still faces various challenges, including the lack of a clear business profile. This business profile is essential to identify the village’s potential, attract investors, and develop long-term work programs. One proposed solution is processing cattle manure using EM4 (Effective Microorganism 4) technology to produce high-quality compost. This compost can enhance soil fertility and support farming activities, which is expected to create a sustainable ecosystem in Gunung Keling Village. Through collaboration between students, BUMDes, village officials, and the community, the village’s economic potential can be developed optimally, balancing economic development with the preservation of local resources.